2001
DOI: 10.1108/13660750110391539
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and intrinsic determinants of quality of work life

Abstract: The objective of this research was to test whether extrinsic, intrinsic or “prior” traits best predict satisfaction with quality of work life (QWL) in health care. Extrinsic traits are salaries and other tangible benefits; intrinsic traits include skill levels, autonomy and challenge. Prior traits are those of the individuals involved, such as their gender or employment status. A survey of employees was conducted in seven different health‐care settings located in the south central region of Ontario, Canada. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 13 publications
4
62
0
2
Order By: Relevance
“…Nurses' satisfaction of pay and fringe benefits has been recognized as one of the most important predictors of QWL Hsu and Kernohan, 2006). Lewis et al (2001) found that pay and benefits explained 40% of the variance in QWL satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' satisfaction of pay and fringe benefits has been recognized as one of the most important predictors of QWL Hsu and Kernohan, 2006). Lewis et al (2001) found that pay and benefits explained 40% of the variance in QWL satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Sosyoloji Araştırmaları Dergisi / Journal of Sociological Research -2014 / 2 As can be understood from above definitions, the quality of work life is a multidimensional structure. Many studies (Groot and Brink 2000;Igbaria et al 1994;Lewis et al 2001;Sirgy et al 2001;Beh 2006;Rose et al 2006;Judge and Bretz 1994;Rethinam and Ismail 2008) have resulted that the quality of work like differ in line with several variables, and it is influenced by several variables at various levels. In the light of these, this study examines whether the quality of work life differs by the working conditions of employees, the perception about protective nature of organisation and demographics, and it explores which variables influences the quality of work life most.…”
Section: The Quality Of Work Life Was Put Forward As a Discipline In mentioning
confidence: 99%
“…Satisfactory, fair and equal salary is one of the milestones of the quality of work life, which means that if the employee is satisfied with his salary in return for his services his quality of work life is high as well (Groot and Brink 2000;Igbaria et al 1994;Lewis et al 2001;Sirgy et al 2001;Bolhari et al 2011). If the organisation does not ensure a satisfactory level of payment, the employee cannot commit himself to his job since he will be thinking of his struggle for survival.…”
Section: Qwl and Salarymentioning
confidence: 99%
“…Revenue growth and profit depend upon the loyalty of the customer and customer loyalty depend upon the customer satisfaction which directly connected to the services provide by the employees' and employees' satisfaction depend upon the dimensions of QWL those has been given by the organisation. In QWL, supervision plays an important role in the individual trait as well as organizational commitment, David Lewis et al (2001). Most research of QWL has done on the academic section which showed faculty relations and community services is the most positive elements in faculty's work life and in present scenario highly satisfaction in the female regarding QWL dimensions compared to male, Linda K. Johnsrud (2006).…”
Section: Discussionmentioning
confidence: 99%